Digital accessibility in Brazilian federal government portals: a replication study - Sousa, Francisco; Moraes, Guilherme; Nehme, Laís; Rivero, Luis; Freire, André; Viana, Davi (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: The Brazilian government has historically promoted digital accessibility guidelines to ensure that Brazilian citizens have equitable access to digital content and services. Problem: In recent years, several portals of Brazilian federal agencies, including those of ministries, have not fully considered the federal government’s digital accessibility guidelines. This problem has resulted in limited access to online information and services for a significant portion of the population. Solution: This paper evaluates the web portals of Brazilian federal agencies in compliance with digital accessibility guidelines. When possible, we evaluate the historical evolution of digital accessibility of such portals. Thus, we show relevant issues where different portals have improved and how they can improve concerning digital accessibility. IS Theory: This paper applies the Theory of Social Shaping of Technology, characterized by a historical approach to web portal accessibility. Method: An inspection was carried out, assisted by tools and manual evaluation, using a descriptive and quantitative approach. We assessed the portals’ compliance with E-MAG and IDG and the use of CMSs, VLibras, high contrast, and screen readers. Summarization of results: We found that the standardization of the portals evaluated regarding the use of CMS Plone, a system that contemplates IDG, decreased the number of portals that offer content translation into other languages. Portals have improved their compliance with E-MAG; all have at least 85Contributions and impact on IS area: Such portals are information systems relevant to all citizens. So, we provide relevant evidence of digital accessibility compliance and challenges in the domain of portals of the Brazilian federal government.